PEMBERDAYAAN PEREMPUAN MELALUI PUBLIC SPEAKING DAN FOTO PRODUK UNTUK MENDUKUNG EKONOMI KELUARGA DI KECAMATAN PURWOKERTO UTARA - Khusna, Itsna Hidayatul; Rahayu, Dian Bestari Santi; Santoso, Edi; Adi, Tri Nugroho; Perdani, Titis (Jurnal Abdi Insani, 2024)
The Covid-19 pandemic has become a challenge for the family economy, including in North Purwokerto District. The problems faced by mothers who drive MSMEs must be faced with changes in consumer behavior to digital media and e-commerce. The problems faced by partners are the lack of public speaking skills and product photography on digital media. Seeing this situation, the community service team provided a solution, that is public speaking and product photography training. This activity aims to improve knowledge and public speaking skills and product photography for promotional purposes on digital media. The methods used in the activity are socialization, training, mentoring, monitoring and evaluation. The results obtained are an increase in the ability to plan public speaking activities, as well as the production of product photos from products made by partners.